2010
DOI: 10.1155/2010/206132
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Bisphosphonate Therapy Could Ameliorate Osteonecrosis: A Complication in Childhood Hematologic Malignancies

Abstract: Osteonecrosis (ON) is a critical complication in the treatment of childhood leukemia and lymphoma. It particularly affects survivors of acute lymphoblastic leukemia and non-Hodgkin lymphoma reflecting the cumulative exposure to glucocorticosteroid therapy. ON is often multiarticular and bilateral, specially affecting weight-bearing joints. A conventional approach suggests a surgical intervention even if pharmacological options have also recently been investigated. We reported two cases of long time steroid-tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…35 Bisphosphonates reduce osteoclast activity and prevent osteocyte and osteoblast apoptosis and thus might reduce the direct toxic effects of chemotherapy on bone cells. [36][37][38][39][40][41][42] Adrenocorticotropic hormone stimulates vascular endothelial growth factor, which enhances osteoblast activity and revascularization of necrotic bone. 43,44 The aforementioned pharmacological interventions might be of most significant impact when applied concomitant with antileukemic treatment associated with hypercoagulopathy and hyperlipidemia to prevent the occurrence of stage I ON and the progression to stage II ON.…”
Section: Pharmacological Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Bisphosphonates reduce osteoclast activity and prevent osteocyte and osteoblast apoptosis and thus might reduce the direct toxic effects of chemotherapy on bone cells. [36][37][38][39][40][41][42] Adrenocorticotropic hormone stimulates vascular endothelial growth factor, which enhances osteoblast activity and revascularization of necrotic bone. 43,44 The aforementioned pharmacological interventions might be of most significant impact when applied concomitant with antileukemic treatment associated with hypercoagulopathy and hyperlipidemia to prevent the occurrence of stage I ON and the progression to stage II ON.…”
Section: Pharmacological Interventionsmentioning
confidence: 99%
“…A detailed summary of pharmacological intervention studies and their outcomes is presented in Table 2. 29,31,35,[37][38][39][40]42,47 Prospective clinical trials are needed to elucidate potential toxicities and thus to facilitate an accurate risk/benefit analysis of these pharmacological interventions. ACTH, adrenocorticotropic hormone; ALCL, anaplastic large cell lymphoma; AML, acute myeloid leukemia; ARCO, association research circulation osseous; AVN, avascular necrosis; BME, bone marrow edema; BMT, bone marrow transplantation; GCS, glucocorticosteroids; HL, Hodgkin lymphoma; HR, high risk; LMW, low molecular weight; NHL, non-Hodgkin lymphoma; n.s., not specified; ON, osteonecrosis; po, by mouth; pts, patients; SR, standard risk.…”
Section: Pharmacological Interventionsmentioning
confidence: 99%
“…17,19,23,26,27 As no proper controls were used in these studies, the real benefit for these drugs was not shown. Side effects consisted of acute phase reactions (headache, fever, nausea, vomiting, malaise), mainly after the first infusion.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
“…Five studies provided data on bisphosphonates, 17,19,23,26,27 one study described an intervention with hyperbaric oxygen therapy, 20 and one study reported on a prostacyclin analog. 24 No studies compared the effectiveness of different antileukemic therapy adjustments as treatment option after the onset of osteonecrosis on the symptoms or radiological progression of osteonecrosis.…”
Section: Non-surgical Interventions For Osteonecrosis In Pediatric Almentioning
confidence: 99%
See 1 more Smart Citation